2014
DOI: 10.1007/s11033-013-2976-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective effects of urinary trypsin inhibitor on astrocytes injured by sustained compression

Abstract: Decreased cell membrane integrity is a primary pathological change observed in traumatic brain injury (TBI) that activates a number of complex intercellular and intracellular pathological events, leading to further neural injury. In this paper, we assessed the effects of urinary trypsin inhibitor (UTI) on astrocyte membrane integrity by determining the percentage of lactate dehydrogenase (LDH) released after sustained compression injury using a hydrostatic pressure model of mechanical-like TBI. Astrocytes isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In in vivo rodent models, cortical compression has led to increased oxidative stress, astrocyte reactivity, and blood-brain barrier permeability (15), and neuronal hyperexcitability (14). Other in vitro studies of sustained compression have observed increased lactate dehydrogenase in response to pressurized 2D cell cultures with neuronal and astrocyte cell lines (16,17). In the present study, we showed strain-dependent decreased cell viability and disrupted neurite network organization in 3D multicellular cortical spheroids.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In in vivo rodent models, cortical compression has led to increased oxidative stress, astrocyte reactivity, and blood-brain barrier permeability (15), and neuronal hyperexcitability (14). Other in vitro studies of sustained compression have observed increased lactate dehydrogenase in response to pressurized 2D cell cultures with neuronal and astrocyte cell lines (16,17). In the present study, we showed strain-dependent decreased cell viability and disrupted neurite network organization in 3D multicellular cortical spheroids.…”
Section: Discussionmentioning
confidence: 92%
“…and implantation of a hemispherical plastic bead inside rat somatosensory cortices to compress the brain statically (15). In vitro SCI studies have typically applied pressurized air to 2D cultures of neural cell lines in pressurized culture chambers (16,17). These studies have begun to provide a time window into cellular events that occur after the exposure of the brain and neuronal cells to forces.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond its inhibition of inflammatory proteases mentioned above, UTI exhibits anti-inflammatory activity and suppresses the infiltration of neutrophils and release of elastase and chemical mediators from them [29,30]. As well, UTI reportedly inhibits the production of TNF-α and IL-1 in LPS-stimulated human monocytes and LPS- or neutrophil elastase-stimulated IL-8 gene expression in HL60 cells or bronchial epithelial cells in vitro [31].…”
Section: Discussionmentioning
confidence: 99%